Selling Your Soul on the Information Superhighway: Consenting to Services in Direct-to-Consumer Tele-Mental Health. Issue 1 (January 2020) - Goldkind, Lauri; Wolf, Lea
Direct-to-consumer tele-mental health services—therapy delivered by video conference, email, and text message—is a burgeoning model of service delivery. The practice of on-demand digital psychotherapy presents ethical questions, as new economic models, service delivery systems, and therapeutic models are introduced. Virtual therapy, now offered on a subscription basis by third-party providers, requires users to accept Terms of Service (ToS) agreements to access services. This article describes the results of a survey in which participants ( n = 579) were asked to compare the values of the Human Rights Framework with the language of one tele-mental health platform's ToS user agreement. Findings suggest that those clients with prior experience with a mental health professional will find the ToS agreements to be the most ethically compromised. Similarly, employed and better educated individuals also found the ToS to be ethically suspect. The most vulnerable of the groups we surveyed, individuals who hold less education and those who are unemployed, may be at most risk for signing consent to a system they do not understand. The study provides one example of the ethical questions that emerge from the introduction of a new model of for-profit service provision in mental health. Recommendations for consumers and practitioners are suggested.